The Effect of Golden Sea Cucumber Extract (Stichopus Hermanii) Administration on Serum Malondialdehyde (MDA) Levels In Wistar Strain White Rats (Rattus Norvegicus) Induced by Aspirin - Anggraeni, Ajeng Hanum Arditha; Pranitasari, Nita; Kurnia, Wachjudi; Wijayaningrum, Lena (Green Publisher Indonesia, 2025)
Drug-Induced Hepatitis (DIH) is a liver function disorder caused by the use of hepatotoxic drugs, which can affect liver metabolism acutely or chronically. A new paradigm suggests that natural-based treatments, such as sea cucumbers, have potential as therapy due to their superior antibacterial bioactivity. This study aims to evaluate the effect of golden sea cucumber extract (Stichopus hermanii) on serum malondialdehyde (MDA) levels in Wistar strain white rats (Rattus norvegicus) induced by aspirin. The study was conducted using a true experimental design with a post-test only control group and random sampling method, involving four treatment groups at the Hyperbaric and Biomolecular Laboratory of Hang Tuah University, Surabaya. The results showed that administering golden sea cucumber extract (Stichopus hermanii) at a dose of 972 mg/kg BW resulted in the highest serum MDA levels in Wistar strain white rats (Rattus norvegicus) induced by aspirin (p=0.001). The study concluded that the administration of golden sea cucumber extract (Stichopus hermanii) significantly affects serum MDA levels in Wistar strain white rats (Rattus norvegicus) induced by aspirin.